2020
DOI: 10.1007/s00421-020-04459-6
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and anthropometric determinants of critical power, W′ and the reconstitution of W′ in trained and untrained male cyclists

Abstract: Purpose This study examined the relationship of physiological and anthropometric characteristics with parameters of the critical power (CP) model, and in particular the reconstitution of W′ following successive bouts of maximal exercise, amongst trained and untrained cyclists. Methods Twenty male adults (trained nine; untrained 11; age 39 ± 15 year; mass 74.7 ± 8.7 kg; V̇O2max 58.0 ± 8.7 mL kg−1 min−1) completed three incremental ramps (20 W min−1) to exhaustion interspersed with 2-min recoveries. Pearson’s … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 36 publications
3
21
1
Order By: Relevance
“…Recent evidence points toward a bi-phasic recovery, enabling rapid recovery of one fraction of W ', followed by a slower recovery of the remaining fraction ( Caen et al, 2021 ). Moreover, a progressive decrease in W' recovery effectiveness during intermittent exercise has recently been suggested, which could account for the decrease in degree of W' expenditure between rounds ( Figure 4 ; Chorley et al, 2019 , 2020 ). As discussed by Gløersen et al (2020) , these two points may explain why athletes in intermittent endurance sports typically choose to expend only a small fraction of their anaerobic energy resources within a supra-maximal bout.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Recent evidence points toward a bi-phasic recovery, enabling rapid recovery of one fraction of W ', followed by a slower recovery of the remaining fraction ( Caen et al, 2021 ). Moreover, a progressive decrease in W' recovery effectiveness during intermittent exercise has recently been suggested, which could account for the decrease in degree of W' expenditure between rounds ( Figure 4 ; Chorley et al, 2019 , 2020 ). As discussed by Gløersen et al (2020) , these two points may explain why athletes in intermittent endurance sports typically choose to expend only a small fraction of their anaerobic energy resources within a supra-maximal bout.…”
Section: Discussionmentioning
confidence: 93%
“…Progressive fatigue development could explain the gradual shift toward less intensive PO relative to CP, resisting accumulation of metabolites that could be detrimental to performance ( Chidnok et al, 2013 ; Davies et al, 2017 ; Hays et al, 2018 ). Indeed, earlier studies have demonstrated that an intermittent workload allows for a greater amount of work done > CP than does a constant workload ( Skiba et al, 2012 ; Chidnok et al, 2013 ; Chorley et al, 2020 ), as long as workloads < CP are available for recovery of W '. The observations from this study showed frequent bouts with various degrees of W' expenditure ( Figures 1B , 4 ), tending to a lower degree of W' expended in later rounds ( Figure 4 ; Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, despite W being associated with thigh muscle size [97,98], . VO 2max [99] and the magnitude of the delta between . VO 2max and CP [99,100], the underlying physiological determinants of W remain largely unknown, necessitating that modelling be conducted on experimental data.…”
Section: W Reconstitutionmentioning
confidence: 99%
“…VO 2max [99] and the magnitude of the delta between . VO 2max and CP [99,100], the underlying physiological determinants of W remain largely unknown, necessitating that modelling be conducted on experimental data. Such a model was developed by Skiba, et al [101], derived from an intermittent cycling protocol of 60 s severe intensity exercise and 30 s at different recovery intensities over four trials.…”
Section: W Reconstitutionmentioning
confidence: 99%
See 1 more Smart Citation